Peculiarities of shipping in the Dnipro basin in 1875-1932 - Roman Dodonov (Cхід, 2018)
The article is devoted to analysis of the dynamics of water transport in the Dnipro basin in the last quarter of 19th - the first third of the 20th century. Under the influence of technological innovations during this period, the structure of the fleet of ships is changing radically, the total tonnage increases, the speed of transportation, the cost of services decreases. The Dnipro begins to work for the needs of the industry, which is booming on its shores. It proves the need of river traffic, its direction, due to the meridional orientation of the river, describes the evolution of the river fleet, steamships too. The article reveals the conditions of navigation and the specifics of navigation on the Dnipro (before the construction of the dam of the Dnipro hydroelectric station).